TARTIB AL-QUR’AN - Moh Abd Azis; Nur Alim Hamzah (IAI Al-Mawaddah Warrahmah Kolaka, 2020)
The composition of the surah and verses in the Al-Qur`an, especially in the Uthmani Mushaf, is not systematic and chaotic, which is due to the interference of friends in the compilation of Al-Qur`an letters during the codification of the Al-Qur`an, so it needs to be reviewed and rearranged. according to the chronology of the decline of the Koran is not correct. This is because if we examine it more deeply, there is a harmony, relationship, and unified unity between the verse and the verse in one letter or between the letter and the letter after it, although at first glance it seems unsystematic. Al-Qur'an contains letters that contain a material, theme, and cover which are arranged in a unified whole which confirms that the Al-Qur`an is methodologically as a book which is undeniable for its systematic and based arrangement of letters. on the very careful planning of the author. And will never be matched by any book either from the literary side or the other side.